THE ROLE OF PUBLIC SPEAKING EXTRACURRICULAR ACTIVITIES IN BUILDING STUDENTS’ SELF-CONFIDENCE AT SD ISLAMIC GLOBAL SCHOOL MALANG - Ema, Ema Rizky Ananda; Marno; Mohamad Zubad Nurul Yaqin (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract Self-confidence is an important aspect of personal development for every individual. With self-confidence, one is able to face challenges, communicate effectively, and optimally develop their potential. For students, self-confidence not only affects academic achievement but also their ability to socialize and express themselves in various situations. The objectives of this study are: (1) to describe and explain the specific role of educators in helping students acquire self-confidence, and (2) to analyze the role of extracurricular activities in building and enhancing students’ self-confidence in elementary school. This research uses a descriptive qualitative approach, which can be used to describe, explain, and analyze why something happens, resulting in accurate findings. The subjects of the research are the principal, the fourth-grade teacher, the public speaking extracurricular mentor, and the students participating in the public speaking extracurricular activities at SD Islamic Global School Malang. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques follow the steps of Miles and Huberman: data collection, data reduction, data presentation, and drawing conclusions. The validity of the findings was checked through source triangulation, technique triangulation, and time triangulation. The results of the study show that the role of educators and public speaking extracurricular activities at SD Islamic Global School Malang play an important role in building students’ self-confidence. The principal provides facilities and encourages parental participation, while the class teacher appreciates and encourages students’ activity through presentation assignments. The extracurricular mentor uses innovative techniques such as role-playing, ad-libbing, announcing skills, and positive self-talk to help students overcome anxiety. Public speaking activities are implemented through careful planning, regular implementation with weekly practices, and periodic evaluations. This program helps students reduce nervousness, improve communication skills, create a positive learning environment, and motivate social and academic engagement, which in turn equips students with essential skills for their future. Keywords: Extracurricular, Public Speaking, Self-Confidence